Narrow-line-mediated Sisyphus cooling in the ^{3}P_{2} metastable state of strontium - Chun-Chia Chen (陳俊嘉); Ryoto Takeuchi; Shoichi Okaba; Hidetoshi Katori (Physical Review Research)
We demonstrate narrow-line-mediated Sisyphus cooling of magnetically trapped strontium (Sr) in the 5s5p^{3}P_{2} state. A 641nm standing-wave, blue detuned from the 5s4d^{3}D_{3}→ 5p4d^{3}F_{4} transition, creates a dissipative optical lattice in the ^{3}D_{3} state. By combining Doppler cooling and Sisyphus cooling on the 5s5p^{3}P_{2}→ 5s4d^{3}D_{3} transition at 2.92µm, we observed efficient cooling of magnetically trapped atoms. By optically pumping the atoms to the 5s5p^{3}P_{0} state, we facilitate continuous outcoupling via a moving optical lattice with twofold improvement in atom number. Our scheme applies to next-generation quantum sensors using continuous ultracold atomic beams.